Produk Legislasi DPRD Perda Nomor 7 Tahun 2022 Tentang Pembinaan Bahasa dan Sastra Daerah di Satuan Pendidikan Sekolah Kota Padang Panjang - Erta Bayu Novriadi (CV. ITTC INDONESIA, 2025)
In the face of advancing times, local languages and literatures must be preserved as markers of pride and cultural heritage. At the request of communities and cultural organisations, local governments in Padang Panjang City and across Indonesia are integrating local languages and literature into the local curriculum. In response to this goal, the Padang Panjang government issued Local Regulation (Perda) No. 7 of 2022 on Education. The purpose of this study is to observe the concept, stages, and implementation in the field. Mrs Maulida Armayulita, S.H., an expert in drafting laws and regulations, was interviewed as part of the descriptive qualitative technique. The results show that the development of the regulation is a long and complicated process that starts from public issues, agenda setting, political legitimacy, policy making, negotiation with DPRD, approval by the regional head, implementation, and evaluation. Cross-sectoral cooperation and rigorous stages are required for this regulation to be successfully implemented to effectively develop and protect Padang Panjang's local language and literature.